"Caracterización físicas, químicas y microbiológicas de la harina del banano morado (Musa ecuminata) red dacca, producidos en los Cantones Mocache, El Empalme y La Maná". - Macías Muñoz, Yander Geovanny (2020)
The research was carried out at the “La María” Campus, belonging to the Quevedo State Technical University, for which six treatments were used to make purple banana flour (Musa acuminata), in which a DCA was applied in accordance factorial AXB, as factor A (locations Mocache, La Maná, El empalme) and factor B (the state of ripeness of green / pinton fruit). The general objective of this study is the characterization of physical, chemical and microbiological properties of banana flour purple. Banana flour was made up of a large amount of carbohydrates. The highest average was obtained by T3a1 with a value of 91.32%, the lowest percentage of humidity was registered in T2a2 with a percentage of 5.07%. The highest content of ash was recorded by T1a2 with a value of 3.18%. The highest percentage of protein was recorded in T2a2 with 1.57. In fiber the highest value was presented by T1a2 with 2.48%. The values obtained in The microbiological analyzes were within the 1529-10AOACC997.02 standard. The values registered in the CIELAB parameters within the NTE INEN 528 standard. The highest concentration was found in the K, Mg, and phosphorus macro minerals, it was also determined that the content of minerals is related to the ash content. Polyphenols have a relationship with fiber content; the highest percentage of carotenoids was recorded in T2a2 with 24.70Ug. Key word: Flour, purple banana, physicochemical characteristics, microbiological analysis.